Peningkatan Kompetensi Guru KKG Sleman Kerjasama UIN Sunan Kalijaga Yogyakarta - Muzakki, M Saidul; Yuliawati, Fitri; Purwati, Heni (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service program is the result of a collaboration between UIN Sunan Kalijaga Yogyakarta and the teacher working group in Sleman. With this collaboration, the quality of teacher working group in Sleman is increasing accompanied by their scientific works. Through this scientific work, teachers can improve positions.